Un compteur « intelligent » pour mesurer les usages de l’eau : l’entrée en scène d’une nouvelle connaissance - Anne-Laure Collard; Patrice Garin; Marielle Montginoul (Développement Durable et Territoires)
In 2013, the Compagnie des Coteaux de Gascogne, water manager in the South West of France, designed a new meter for agricultural withdrawals. Unlike conventional manual meters read two to three times a year, it automatically transmits the previous day’s consumption and average flow rate to the manager. However, beyond a hydraulic logic, how does this “act of measuring”, the production of this new knowledge about water reconfigure the relationship to water of those who use it? Based on an empirical study, the aim of this article is to understand the implications related to this so-called “intelligent” object by the water engineers and the applications on social relations relating to water. From precision concerns to water sharing concerns, the meter becomes in turn an object of knowledge, a means of control and monitoring, and a support for negotiation.